Analysis Of Employee Career Development At The Office Of The Apparatus Human Resources Development Personnel Agency In Sinjai Regency - Mochtar Luthfi M; Ratih Azis; Tetty Dwiyanti (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims 1). To analyze the developmentn career of employees in the Office of the Human Resources Development Personnel Agency of the Apparatus in Kabupaten Sinjai, 2). To analyze the factors hindering the career development of employees in the office of the human resources development personnel agency of the Sinjai District apparatus. The type of research used is qualitative research with data collection techniques through observation, interviews, documentation with data analysis through data collection, data reduction, data presentation and drawing conclusions. The results showed that: 1). Analysis of Employee Career Development at the Office of the Human Resources Development Personnel Agency Apar atur in Sinjai Regency, such as work experience, competence, education and training, work achievements, superior attitudes have shown good results because they have carried out their duties as The State Civil Apparatus is in accordance with the rules applied to Civil Servants, as well as efforts to support the career development of employees. However, in career development there are several conditions, so that employees who are constrained at the education level need to continue their education to develop their careers. 2). Factors that hinder the career development of employees in the office of the personnel agency human resource development apparatus in Sinjai District are work experience, attitude of superiors, vacancies because Career development depends on the needs of the agency and is one of the requirements in employee career development.